59 The stem cell unrelated donor search during COVID19. (23rd February 2023) - Hill, Annette; Finch, Maria; Mead, Rachel; Young, Lindsey; Farish, Susan
Abstract : Background: In Stem Cell Transplants approximately two thirds of donors are identified and used from unrelated donor registries. In January 2020, we considered the impact that Covid19 infections and restrictions would have on donor availability. We identified that we needed to change our practice to ensure we could continue the SCT procedures which are critical for patients. Methods: In January 2020, the Joint United Kingdom Blood Transfusion and Transplantation Service Professional Advisory committee (JPAC) changed the Tissue and cell donor selection guidelines. The risk and restrictions of Covid19 caused significant challenges including logistical issues for product delivery. Donor deferrals at medical assessments increased from 14% to 29% and overall activity in the UK was 75% of usual provision. Best practice was established and agreed with the donor registries. As per NICE guidelines, cryopreservation of all stem cell products was recommended with fresh donations considered according to patient condition. Back up donors were identified where possible. All donors were tested for Covid 19 on day of medical and harvest to ensure effective screening. We carried out 58 stem cell procedures from unrelated donors in 2020 and 56 in 2021. This activity is comparable to previous years. We secured stem cell products from Germany, USA, Korea, Poland, Turkey, Greece, Switzerland, the Netherlands and the UK. We analysed our data to assess if any delays occurred. Ethical approval was not required for this service evaluation. Results: SCT activity was maintained throughout Covid19 with only postponement of elective SCT's which was assessed to be in the patient's best interest. Discussion: We were able to adapt our practice to the benefit of our patients in unique and challenging circumstances. Conclusion: We implemented measures which enabled BMT activity to continue throughout the acute Covid19 period despite challenges with new variants and further restrictions.